2022
DOI: 10.7759/cureus.21665
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Diffuse Alveolar Hemorrhage With COVID-19 Vaccination

Abstract: With the growing rates of vaccination against coronavirus disease 2019 (COVID-19) across the globe, rare side effects have been increasingly noticed on a post-marketing basis. Cases of myocarditis and pericarditis have been reported in the literature following COVID messenger RNA (mRNA) vaccination. However, diffuse alveolar hemorrhage (DAH) following vaccination has not been reported. DAH is a life-threatening clinicopathological entity characterized by bleeding into the alveolar space from pulmonary microvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, after initiating treatment of AAV relapse, the titer of anti-MPO antibody decreased coinciding with improvements in pulmonary hemorrhage (Figure 3), which is similar to a previous case report (31). In addition, Sharma et al reported a unique case demonstrating that diffuse alveolar hemorrhage occurred 8 h after the first dose of COVID-19 mRNA vaccination without any evidence of immunological complications such as elevation of anti-MPO antibody titers (32). Infection and tumor, two major inciting factors for AAV relapse (33)(34)(35) and other immunological underlying diseases for pulmonary-renal syndrome, such as antiglomerular basement membrane (GBM) disease: Goodpasture syndrome, systemic lupus erythematosus, and dual ANCA and anti-GBM positive disease (36) have been ruled out.…”
Section: Discussionsupporting
confidence: 83%
“…However, after initiating treatment of AAV relapse, the titer of anti-MPO antibody decreased coinciding with improvements in pulmonary hemorrhage (Figure 3), which is similar to a previous case report (31). In addition, Sharma et al reported a unique case demonstrating that diffuse alveolar hemorrhage occurred 8 h after the first dose of COVID-19 mRNA vaccination without any evidence of immunological complications such as elevation of anti-MPO antibody titers (32). Infection and tumor, two major inciting factors for AAV relapse (33)(34)(35) and other immunological underlying diseases for pulmonary-renal syndrome, such as antiglomerular basement membrane (GBM) disease: Goodpasture syndrome, systemic lupus erythematosus, and dual ANCA and anti-GBM positive disease (36) have been ruled out.…”
Section: Discussionsupporting
confidence: 83%
“…We initiated intravenous antibiotics to cover Staphylococcus Aureus and Gram Negative bacteria, as well Anti-Tuberculous Treatment; and then proceeded to escalate them when no improvement was being seen as well as adding anti-fungal and anti-viral medications but to no avail. There have been a few documented cases of DAH secondary to Covid 19 infection 9,10 , but in our patient 2 sets of Covid PCR were negative, but there was a growth on non-pandemic Coronavirus on our Viral Panelwhich seemed to be unlikely as the primary cause of the patient's condition and severity.…”
Section: Discussionmentioning
confidence: 58%
“…Primary pulmonary hemorrhage can occur after mRNA COVID-19 vaccination [5][6][7]. The U.S. Food and Drug Administration Center for Biologics Evaluation and Research (CBER) regulatory window of concern for a novel genetic product, such as the BNT162b2 mRNA COVID-19 vaccine, is 5-15 years [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that 71% of SAEs occurred in only 4.2% of BNT162b2 batches [4]. Pulmonary hemorrhage has been reported as a serious adverse event following COVID-19 vaccination with BNT162b2 and mRNA-1273 (Moderna) [5][6][7]. Here, we report an autopsy case of a 47-year-old male that died unexpectedly from pulmonary hemorrhage over one year after primary COVID-19 vaccination with BNT162b2 and perform an investigation into the BNT162b2 batch he received.…”
Section: Introductionmentioning
confidence: 98%